Antibiotic Prophylaxis with Trimethoprim-Sulfamethoxazole versus No Treatment after Mid-to-Distal Hypospadias Repair: A Prospective, Randomized Study. (26th March 2018) - Roth, Elizabeth B.; Kryger, John V.; Durkee, Charles T.; Lingongo, Melissa A.; Swedler, Ruth M.; Groth, Travis W.
Abstract : Purpose . To evaluate the impact of prophylactic antibiotics after distal hypospadias repair on postoperative bacteriuria, symptomatic urinary tract infection, and postoperative complications in a prospective, randomized trial. Materials and Methods . Consecutive patients aged 6 months to 2 years were enrolled at our institution between June 2013 and May 2017. Consenting patients were randomized to antibiotic prophylaxis with trimethoprim-sulfamethoxazole versus no antibiotic. Patients had catheterized urine samples obtained at surgery and 6–10 days postoperatively. The primary outcome was bacteriuria and pyuria at postoperative urine collection. Secondary outcomes included symptomatic urinary tract infection and postoperative complications. Results . 70 patients consented to the study, of which 35 were randomized to receive antibiotics compared to 32 who did not. Demographics, severity of hypospadias, and type of repair were similar between the groups. Patients in the treatment group had significantly less pyuria (18%) and bacteriuria (11%) present at stent removal compared to the nontreatment group (55% and 63%;p = 0.01 andp < 0.001, resp.). No patient had a symptomatic urinary tract infection. There were 11 postoperative complications. Conclusions . Routine antibiotic prophylaxis appears to significantly decrease bacteriuria and pyuria in the immediate postoperative period; however, no difference was observed in symptomatic urinary tract infection or postoperative complications. Clinical Trial Registration NumberNCT02593903 .